Structural enrichment for laboratory mice: exploring the effects of novelty and complexity - Bohn, Lena; Bierbaum, Louisa; Kästner, Niklas; von Kortzfleisch, Vanessa Tabea; Kaiser, Sylvia; Sachser, Norbert; Richter, S. Helene (Frontiers in Veterinary Science, 2023)
Providing structural enrichment is a widespread refinement method for laboratory rodents and other animals in captivity. So far, animal welfare research has mostly focussed on the effect of increased complexity either by accumulating or combining different enrichment items. However, increasing complexity is not the only possibility to refine housing conditions. Another refinement option is to increase novelty by regularly exchanging known enrichment items with new ones. In the present study, we used pair-housed non-breeding female C57BL/6J and DBA/2N mice to investigate the effect of novelty when applying structural enrichment. We used a double cage system, in which one cage served as home cage and the other as extra cage. While the home cage was furnished in the same way for all mice, in the extra cage we either provided only space with no additional enrichment items (space), a fixed set of enrichment items (complexity), or a changing set of enrichment items (novelty). Over five weeks, we assessed spontaneous behaviours, body weight, and extra cage usage as indicators of welfare and preference. Our main results showed that mice with access to structurally enriched extra cages (complexity and novelty) spent more time in their extra cages and had lower latencies to enter their extra cages than mice with access to the extra cages without any structural enrichment (space). This indicates that the mice preferred the structurally enriched extra cages over the structurally nonenriched space cages. We found only one statistically significant difference between the novelty and complexity condition: during Week 3, novelty mice spent more time in their extra cages than complexity mice. Although we did not detect any other significant differences between the novelty and complexity condition in the present study, more research is required to further explore the potential benefits of novelty beyond complexity.